Evolution, genomic analysis, and reconstruction of isobutanol tolerance in Escherichia coli - Shota Atsumi; Tung‐Yun Wu; Iara M P Machado; Wei‐Chih Huang; Pao‐Yang Chen; Matteo Pellegrini; James C Liao (Molecular Systems Biology)
Abstract Escherichia coli has been engineered to produce isobutanol, with titers reaching greater than the toxicity level. However, the specific effects of isobutanol on the cell have never been fully understood. Here, we aim to identify genotype–phenotype relationships in isobutanol response. An isobutanol‐tolerant mutant was isolated with serial transfers. Using whole‐genome sequencing followed by gene repair and knockout, we identified five mutations (acrA, gatY, tnaA, yhbJ, and marCRAB) that were primarily responsible for the increased isobutanol tolerance. We successfully reconstructed the tolerance phenotype by combining deletions of these five loci, and identified glucosamine‐6‐phosphate as an important metabolite for isobutanol tolerance, which presumably enhanced membrane synthesis. The isobutanol‐tolerant mutants also show increased tolerance to n‐butanol and 2‐methyl‐1‐butanol, but showed no improvement in ethanol tolerance and higher sensitivity to hexane and chloramphenicol than the parental strain. These results suggest that C4, C5 alcohol stress impacts the cell differently compared with the general solvent or antibiotic stresses. Interestingly, improved isobutanol tolerance did not increase the final titer of isobutanol production.